The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.5455/2320-6012.ijrms20131119
|View full text |Cite
|
Sign up to set email alerts
|

Serum magnesium in pregnancy induced hypertension

Abstract: Background: PIH is a major cause of maternal & perinatal morbidity & mortality worldwide because of its complications. The etiology of PIH is uncertain but appears to be related to uteroplacental ischaemia. Magnesium is one of the principle macronutrients, regulates vascular tone, causes relaxation of muscles of uterus and decreases excitability of nerves & muscles. Hence the study was planned to estimate and compare the levels of magnesium between women with PIH and normal pregnant women. Methods: The study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The present study also found that women with preeclampsia had a significantly higher mean serum calcium-magnesium ratio than did women without preeclampsia (1.94±0.957 vs 2.54±0.775; P =0.0001). This finding agrees with a study conducted by Bandebuche et al that showed the mean ratio of calcium-magnesium in the preeclampsia group was lower than that of the non-preeclampsia group [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study also found that women with preeclampsia had a significantly higher mean serum calcium-magnesium ratio than did women without preeclampsia (1.94±0.957 vs 2.54±0.775; P =0.0001). This finding agrees with a study conducted by Bandebuche et al that showed the mean ratio of calcium-magnesium in the preeclampsia group was lower than that of the non-preeclampsia group [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Nahar et al reported that the estimation of serum magnesium during the antenatal period can help predict preeclampsia and prevent eclampsia [ 26 , 27 ]. Three studies, conducted in 2013, 2018, and 2019, showed that mean calcium levels in patients with preeclampsia were significantly higher than those in patients without preeclampsia [ 28 – 30 ]. There are also some studies that reported no significant differences in serum magnesium levels between women with and without preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Abruption due to gestational hypertension was seen in 10% and 21% of cases among the local and regional populations, respectively [ 1 , 7 , 9 ]. The risk of abruption placenta was also found to be 2.4 times among women with chronic hypertension and not surprisingly increased further in the presence of preeclampsia or fetal growth retardation [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy-induced hypertension (PIH) is the onset of new arterial hypertension in a pregnant woman after the 20th week of gestation, during labour or puerperium in previously normotensive women without the presence of protein in the urine [ 1 , 2 ]. It occurs in about 6-8% of all pregnancies [ 1 , 3 ]. The incidence of PIH varies throughout the world; however, the incidence is higher in developing countries [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 Serum magnesium progressively declines during pregnancy reaching a nadir at 34 weeks and then rises up to term. 17 Statistically significant fall in serum magnesium has been observed in pre-eclampsia and with remarkable reduction in eclampsia. 18 In study done by Indumathi V et al, serum magnesium decreased in the study group when compared to control group which was significant.…”
Section: Serum Magnesiummentioning
confidence: 98%